E-COMMERCE CONSUMER PROTECTION At TOKOPEDIA - Muhajir Muhajir (Al-Amwal : Journal of Islamic Economic Law, 2019)
This study aims to determine and understand the legal principles in protecting the rights of e-commerce consumers who transact on Tokopedia. This research is library research (library research) with a normative approach because it is a research that analyzes written regulations related to consumer protection in conducting electronic transactions on Tokopedia. The data source is secondary data in documents, reports, books, and other publications that support this research. The results show that e-commerce consumers transact on Tokopedia are in a weak position that can experience fraud from business actors who open stalls on the Tokopedia site. In protecting and safeguarding consumer rights, Tokopedia must establish strict rules and procedures for business actors conducting business activities on Tokopedia based on Law No. 8 of 1999 concerning consumer protection, Law No. 11 of 2008 concerning Electronic Information and Transactions Government Regulations Number 82 of 2012 concerning Implementation of Electronic Systems and Transactions.